(untitled) (ModaPalavra e-periódico, 2020)
This work aimed to take an approach on 3D printing technology in the fashion system, and the importance of postponement strategies, which are leading to greater information sharing in the production chain of this sector. It is also mentionate a way to intr oduce mass customization based on digital networks and other emerging technologies that has been breaking the traditional B2C (business to consumer) paradigm. This study features three entry - level machinery design projects, non - industrial 3D printers, and issues related to new ways of consumption. It can be concluded that 3D printing manufacturing is associated with lean production with few material surpluses or scraps, but when it comes to buying and shipping the product these issues still seem not to be c onsidered.